Low carbohydrate diets containing soy protein and fish oil slow the growth of established NNK-induced lung tumors. (26th March 2020) - Elisia, Ingrid; Hay, Mariah; Cho, Brandon; Yeung, Michelle; Kowalski, Sara; Wong, Jennifer; Lam, Vivian; Larsen, Meegan; Krystal, Gerald
Abstract: We recently found that a diet composed of 15% of total calories as carbohydrate (CHO), primarily as amylose, 35% soy protein and 50% fat, primarily as fish oil (FO) (15%Amylose/Soy/FO) was highly effective at preventing lung nodule formation in a nicotine-derived nitrosamine ketone (NNK)-induced lung cancer model. We asked herein whether adopting such a diet once cancers are established might also be beneficial. To test this, NNK-induced lung nodules were established in mice on a Western diet and the mice were then either kept on a Western diet or switched to various low CHO diets. Since we previously found that sedentary mice develop more lung nodules than active mice, we also compared the effect of exercise in this cancer progression model. We found that switching to a 15%Amylose/Soy/FO diet reduced lung nodules and slowed tumor growth with both 'active' and 'sedentary' mice. Ki67, cleaved caspase 3 and Terminal Deoxynucleotidyl Transferase-Mediated dUTP Nick End Labeling assays suggested that the efficacy of the 15%Amylose/Soy/FO in lowering tumor nodule count and size was not due to a reduction in tumor cell proliferation, but to an increase in apoptosis. The 15%Amylose/Soy/FO diet also significantly lowered liver fatty acid synthase and 6-phosphofructo-2-kinase/fructose-2, 6-biphosphatase 3 expression, pointing to a global metabolic switch from glycolysis to fatty acid oxidation. Mice fed the 15%Amylose/Soy/FO diet also had significantly reduced plasma levels of interleukin (IL)-1β, IL-6 and tumor necrosis factor α. These results suggest that the 15%Amylose/Soy/FO diet may slow tumor growth by suppressing proinflammatory cytokines, inducing a metabolic switch away from glycolysis and inducing apoptosis in tumors. Abstract : A low carbohydrate diet containing resistant starch, soy protein and fish oil was found effective at slowing the growth of established lung tumors in mice by inducing apoptosis, reducing inflammation and suppressing glycolysis.